Tingkat Keterbacaan Wacana pada Buku Teks Bahasa Indonesia Kurikulum Merdeka - Basri, Muh. Bahly; Nojeng, Asis; Ilham, Muhammad; Gaffar, Muh. Syukri (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2024)
Indonesian language learning requires students to develop process skills. One of the process skills that must be mastered is the ability to complete a fill-in-the-blank test. The ability to complete a fill-in-the-blank test is very important because it can provide quantitative information that is easy to understand. The skill of reading or completing a fill-in-the-blank test in the form of verbal and nonverbal sentences is very necessary, especially in the field of Indonesian language. This study aims to determine the level of discourse readability in the Indonesian language textbook Class X Independent Curriculum. This research is descriptive research with a quantitative approach. This research was conducted by measuring the readability of discourse based on thecloze technique. The text tested was the text of the observation report in the grade X Indonesian language book published by the Ministry of Education and Culture revised 2021. The results showed that the highest percentage of text readability level categories was the easy category (independent) as many as 67.5% or 81 students, the medium category (instructional) 20.8% or 25 students and the difficult category (frustration) 11.7% or 14 students. The right choice of words (diction) and the application of simple sentence structures (simplex) make it easy for students to understand the content of the text. Thus, the observation report text is suitable to be applied at grade X level.